Rediscovery and range extension of Ciliopagurus liui Forest, 1995 and description of a new species of Pagurus Fabricius, 1775 (Crustacea: Decapoda: Anomura: Paguroidea) from the Kerala State, southwestern India - Komai, Tomoyuki; Reshmi, Rema; Kumar, Appukuttan Nair Biju (Zootaxa, 2013)
Two species of paguroid hermit crabs, Ciliopagurus liui Forest, 1995 (Diogenidae) and Pagurus spinossior n. sp. (Paguridae), are reported from the Kerala State, southwestern India. Ciliopagurus liui, is first recorded from the Indian Ocean. This species was originally described on the basis of a single male specimen from the Tonkin Gulf in the South China Sea, though its geographical range also included Japan, based on literature. Supplemental description and illustrations are provided for better understanding of the diagnostic features of this little known species. Pagurus spinossior n. sp., described on the basis of a single male specimen, appears closest to P. spinulentus (Henderson, 1888), known only by the holotype from the Philippines, but the lack of spinules on the dorsal margins of the dactyli of the second pereopods, the different shape of the anterior lobe of the thoracic sternite 6, and the more numerous spines on the terminal to posterior margins of the telson distinguish the new species from P. spinulentus.